Examination of Reproductive Performance of Roe Deer (Capreolus capreolus) in Hungary - Majzinger, István (Acta Agraria Debreceniensis, 2004)
The objective of the research partly is to compare the reproduction performance of the populations living in different regions with regard to some special characteristics (age, condition).When estimating the age through tooth wear and cementum-layer-counting there was a difference of 0.87 years in favour of the first one (r=0,840; p